MANAJEMEN PEMBELAJARAN PJOK BERBASIS KARAKTER DAN ADAPTASI KONDISIONAL DI SEKOLAH DASAR - Satrio Maulana; Elfera Rizky; Muhammad Faisal (Journal of Physical Activity and Sports (JPAS), 2026)
This study aims to describe the experiences of physical education teachers in dealing with situational challenges, managing character development, and systematically evaluating teaching failures. A qualitative approach using a phenomenological study design was employed in this research. The participant was a physical education teacher at SD IT Iskandar Muda, selected through purposive sampling. Data were collected through semi-structured interviews, field notes, and documentation from daily teaching journals. Data analysis followed Colaizzi’s phenomenological procedures. The results indicate that the teacher’s most challenging experience was fostering character development, not merely physical skills. Adapting to situational constraints such as weather changes and transition times required contingency plans and high flexibility. The most effective learning model is a combination of TPSR, peer tutoring, drills, and differentiation. Evaluating failures through daily journals was proven to improve learning quality continuously. This study concludes that the success of Physical Education and Health (PJOK) learning is not only measured by mastery of movement but also by students’ independence and teachers’ ability to reflect on failures. The implications of this study are the need for training in transition class management and the development of failure reflection journals for physical education teachers.